Folklore and Mythological Motives in the Works of Ch. Aitmatov - Ilshatovna Nureeva, Gulshat; Ihsanovna Mingazova, Liailia; Ilyich Rogachev, Vladimir; Sagitovna Sayfulina, Flera (International Journal of Criminology and Sociology, 2022)
The purpose of this article is to analyze and evaluate the place of folklore and mythological motifs in the heritage of Chingiz Aitmatov, to reveal the connection between folklore and national character. The work of Ch. Aitmatov and folk culture are closely interconnected. This multilevel context, in our opinion, is as follows: 1) appeal to the folk culture at the level of folklore and mythological motives; 2) appeal to fundamental universal values - conscience, honor, goodness, love, self-sacrifice, procreation, a succession of generations; 3) reconstruction of the ethnic codes of folk culture, mythologies, historical chronotope, nation; 4) the use of ethnographic and ethno-aesthetic micro-units to create the artistic space of works; 5) the use of folk texts, linguistic turns, stylistic means to create poetics of works; 6) recreation of the model of behavior, the lifestyle of a working person, people and its presentation at the level of semantic codes of poetry; 7) the inclusion of worldviews, people's view of life, what is happening, the moral assessment of events, actions by ordinary people as a litmus test of truth; 8) appeal to God, to the questions of God-seeking as the moral support of the people, society. And so, the article is devoted to the interaction of the writer's work with folk culture, multi-genre oral folk art. The basic paradigms, causes, and mechanism of the inclusion of myths, legends, legends, parables in works of art are studied. The role of folk culture in the writer's works is considered.